2023
DOI: 10.1038/s41398-023-02322-8
|View full text |Cite
|
Sign up to set email alerts
|

Low protein-induced intrauterine growth restriction as a risk factor for schizophrenia phenotype in a rat model: assessing the role of oxidative stress and neuroinflammation interaction

Abstract: A large body of evidence suggests that intrauterine growth restriction (IUGR) impedes normal neurodevelopment and predisposes the offspring to cognitive and behavioral deficits later in life. A significantly higher risk rate for schizophrenia (SZ) has been reported in individuals born after IUGR. Oxidative stress and neuroinflammation are both involved in the pathophysiology of SZ, particularly affecting the structural and functional integrity of parvalbumin interneurons (PVI) and their perineuronal nets (PNN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…While a wealth of data exist for the neuronal component, our understanding of its impact on other cell types such as oligodendrocytes, astrocytes, and microglia remains limited. To our knowledge, only one study has revealed that gestational protein restriction in rats induces microglia to a state of hyperactivity, elevating oxidative stress and neuroinflammatory markers in adult stages ( 113 ). In addition, exploring the role of the placenta as a fetal caretaker in abnormal nutritional conditions deserves more attention ( 114 , 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…While a wealth of data exist for the neuronal component, our understanding of its impact on other cell types such as oligodendrocytes, astrocytes, and microglia remains limited. To our knowledge, only one study has revealed that gestational protein restriction in rats induces microglia to a state of hyperactivity, elevating oxidative stress and neuroinflammatory markers in adult stages ( 113 ). In addition, exploring the role of the placenta as a fetal caretaker in abnormal nutritional conditions deserves more attention ( 114 , 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…[50] (×20), [51]; [89] WFA, Aβ (Amylo-Glo), CD68, Iba1, Thioflavin-S, PV, Aggrecan, Crtl1, GAD65/67, vGlut1, Cat-301, calretinin, MAP2, VGAT, brevican Schizophrenia, bipolar disorder [42] (×20/0.5; ×63/1.4); [99]; [100] (×20/0.5); [101] (×20; ×40) WFA, PV, HNK-1, S100-β, CS56, MMP9, 8-oxo-dG, CD68, Iba1 Substance use disorder [102] (×20/0.7; ×63/1.4); [103] (×20/0.75; ×20/0.7); [104] (×40); [105] (×63/1.4); [106] (×40), [107]; [32] (×20/0. Hibernation-like state [113] AI-assisted Normal brain [34,36] WFA, parvalbumin…”
Section: Confocal Microsopymentioning
confidence: 99%
“…Maternal undernutrition leads to intrauterine which several studies have linked with lower IQ scores [89]. A systematic review and meta-analysis of 35 studies involving over 8,000 children found that those born with intrauterine growth restriction (IUGR) had, on average, lower IQ scores than those born with normal birth weights [90]. In addition to lower IQ, IUGR has also been linked to an increased risk of schizophrenia.…”
Section: Nutritionmentioning
confidence: 99%